2018
DOI: 10.1002/cncy.22067
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and perceptions of urgent and alert values in surgical pathology and cytopathology: A survey of clinical practitioners and pathologists

Abstract: In previous editorials, Chapman and Otis in 2011 and Layfield in 2014 have summarized much of the work responsible for establishing the concept of critical diagnoses in surgical pathology and cytopathology. Both editorials end with a list of 8 key policy points needed for an effective strategy of handling and communicating critical diagnoses. We have developed and distributed a Web‐based survey to elicit clinicians’ attitudes regarding many of those key policy points, such as how, when, and to whom critical di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…If an institution treats both categories exactly the same way, the addition of another category probably serves only to unnecessarily increase complexity of the communication process. Other authors have proposed different terms 21,22 . The ADASP survey found that approximately one-quarter of surveyed institutions used the term critical, another one-quarter used the CAP/ADASP terminology, and almost half of institutions surveyed used another term in their policy 6 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If an institution treats both categories exactly the same way, the addition of another category probably serves only to unnecessarily increase complexity of the communication process. Other authors have proposed different terms 21,22 . The ADASP survey found that approximately one-quarter of surveyed institutions used the term critical, another one-quarter used the CAP/ADASP terminology, and almost half of institutions surveyed used another term in their policy 6 …”
Section: Discussionmentioning
confidence: 99%
“…The ADASP survey, on the other hand, did find some areas of relative agreement 6 . As these 2 studies are the largest multi-institution surveys performed to date, our discussion will focus primarily on these articles; however, other smaller multi-institutional studies have been published with similar findings 7,15 ; in addition, a number of single-institution publications have suggested candidate urgent diagnoses in anatomic pathology or surgical pathology, 2,16,21,22 cytopathology, 9,19,23 pediatric pathology, 10 dermatopathology, 20 and ophthalmologic pathology 24 . The diagnoses typically considered fall into 4 broad categories: malignancy, infection, other diagnoses, and technical/diagnostic issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As there were no established criteria for critical or unexpected results in the studied centers, a multiple-choice questionnaire was developed. The list of diagnoses was chosen by the authors according to previous surveys and the authors' experience to represent diagnoses that might be critical [ 3 , 6 10 ] (Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…It is also known as "critical diagnosis," "urgent diagnosis," and treatable, immediately life-threatening diagnosis." Regardless of the attributed terms, an immediate report to a healthcare provider is necessary for taking the required medical actions [ 3 ].…”
Section: Introductionmentioning
confidence: 99%